Surgical treatment of multiple maxillary dentigeral cysts in pediatric patient (Research, Society and Development, 2021)
The dentigerous cyst is a benign lesion of origin related to odontogenic development that surrounds the crown of an unerupted dental element at the level of the cementoenamel junction. Its pathogenesis is still a matter of debate, but its development is believed to be the result of the accumulation of fluid between the reduced epithelium of the enamel organ and the crown of the involved tooth. Studies claim that the prognosis is extremely favorable when the lesion is completely removed, which prevents recurrence and excludes the possibility of malignant transformation of the lesion. This paper aims to report a case of recurrent dentigerous cyst in the maxilla. Discussing diagnosis, surgical treatment and investigation of systemic causes. The case report, as evidenced by scientific research, shows the possibility of this pathology acquiring large proportions, causing several interferences in the patient's aesthetics and function. Dentigerous cysts are relatively common lesions during the clinical routine of the dental surgeon, however, even if rare, they can recur. Its presence can cause several aesthetic and functional problems for the patient and, therefore, the importance of radiographic exams for the identification and diagnosis of these pathologies is observed, in order to avoid further complications.